Mapping COVID vulnerability in relation to drug and alcohol recovery residence availability across the United States - Amy A. Mericle; Deidre Patterson; Meenakshi S. Subbaraman; Jason Howell; Dave Sheridan; Thomasina Borkman; Jayla Burton; Katherine J. Karriker-Jaffe (BMC, 2023)
Abstract Recovery housing is an important resource for those in recovery from substance use disorders. Unfortunately, we know little about its relationship to key community health risk and protective factors, potentially limiting the role it could play as a broader health resource. Leveraging county-level data on recovery residences from the National Study of Treatment and Addiction Recovery Residences (NSTARR), this study used multilevel modeling to examine Community COVID Vulnerability Index (CCVI) scores as well as availability of COVID testing and vaccination sites in relation to recovery housing. CCVI composite scores were positively associated with recovery housing availability. Analyses using CCVI thematic sub-scores found that population density and number of churches were positively associated with recovery housing availability, while epidemiological factors and healthcare system factors were negatively associated with recovery housing availability. In counties with recovery housing, there also was a positive association between CCVI and both COVID testing and vaccination availability. Recovery residences tend to be located in areas of high COVID vulnerability, reflecting effective targeting in areas with higher population density, more housing risk factors, and other high-risk environments and signaling a key point of contact to address broader health issues among those in recovery from substance use disorders.